All-solid-state thin film battery based on well-aligned slanted LiCoO2 nanowires fabricated by glancing angle deposition - Yoon, Miyoung; Lee, Seunghwan; Lee, Daehee; Kim, Joosun; Moon, Jooho (ELSEVIER SCIENCE BV, 2017)
We fabricated all-solid-state thin film batteries based on well-aligned slanted LiCoO2 nanowires by glancing angle deposition, as a facile template-free method in order to increase the electrochemically active site, i.e., the contact area between the solid electrolyte and the electrode. A highly porous thin film composed of well-separated slanted LiCoO2 nanowires not only facilitates the penetration of solid electrolyte phase into,the cathode, but also alleviates the thermally and mechanically induced stresses during post annealing and electrochemical cycling. The all-solid-state thin film battery based on the well-aligned slanted LiCoO2 nanowires, whose contact area between electrolyte and electrode was three times as high as that of a dense thin film, could provide additional migration pathways for lithium ion diffusion due to the enlarged reaction sites. This resulted in enhanced electrochemical kinetics, thereby leading to better rate capability and long-term cyclic stability as compared to the dense LiCoO2 thin film. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: LITHIUM ION BATTERIES; CATHODES; DEVICES; ARRAYS; ELECTROLYTES; ORIENTATION; TEMPLATE